Letter (copy) : Conference, March 10th and 11th - Tewson, Vincent
022_0018-001 HVT/FP/214 Secretary's. 19th February, 1937. Mr. W. Schevenels, International Federation of Trade Unions, 9, Avenue D'Orsay, Paris VIIe. Dear Mr. Schevenels, Conference, March 10th and 11th. I desire to confirm the telegram which I sent this morning in the following terms: "CENTRAL HALL WESTMINSTER DEFINITELY BOOKED MARCH 10TH AND 11TH. LETTER FOLLOWS. TEWSON." I may say that we had considerable difficulty in booking a suitable hall at such short notice, and we left the Central Hall as our last enquiry on account of the fact that they do object to meetings of a political character. I have made quite certain, however, that in the case of our Conference no objection will be raised, and the Conference may now be convened with a definite assurance that the Central Hall will be available. Yours sincerely, Assistant Secretary. 292/946/22/17